Evolution and trends in retailing: insights from International Journal of Retail & Distribution Management - Wang, Siqi; Cheah, Jun-Hwa; Lim, Weng Marc; Kumar, Satish; Lim, Xin-Jean; Towers, Neil (Emerald Group Publishing, 2024)
Purpose – This study aims to embark on a bibliometric journey through the International Journal of Retail & Distribution Management (IJR&DM) to delve into its rich repository of applied retailing research. Design/methodology/approach – 626 publications in IJR&DM between 2015 and 2023 have been retrieved from Scopus for performance analysis of the journal’s publication (productivity) and citation (impact) trends as well as a science mapping of the journal’s collaborators (contributors) and major themes (contributions). Findings – The performance analysis highlights the growth in the productivity and impact of IJR&DM alongside its most cited publications, most prolific contributors, most relied-on journals, as well as the authors, institutions, countries, and journals that the journal has impacted the most. The co-authorship analysis reveals the collaboration (i.e., international with a high concentration in Europe and North America along with an emerging presence in Asia) of IJR&DM. Keyword co-occurrence analysis and bibliographic coupling reveal eight themes. Our exploration revealed close interconnections among various domains including retailing and adaptive strategies, channel strategies, customer experience, market innovations, operations management, relationship marketing, shopping motivation, and sustainability. Research limitations/implications – Although this study delivers a state-of-the-art overview of the retail industry through the scientific contributions from IJR&DM, it remains limited to the insights from a single authoritative source of knowledge on retailing. Originality/value – No review, to date, has been conducted for IJR&DM. This study provides the inaugural retrospective of the scientific contributions of IJR&DM, outlining publication and citation trends alongside the intellectual structure of its body of knowledge on retailing. Theoretically, this retrospective is pivotal in charting the intellectual growth and thematic nuances inherent in retail research. Practically, this study serves as a guide for practitioners, enabling them to make strategically informed decisions and craft forward-looking strategies in sync with current realities.